DEVELOPMENT OF A COMPUTATIONAL THINKING TEST INSTRUMENT BASED ON THE CLASSPOINT LEARNING APPLICATION WITHIN A STEAM PROJECT - Deviana; Ni Putu Desy Damayanthi; I Gede Putu Adhitya Prayoga (RADJA PUBLIKA, 2025)
Computational Thinking (CT) is a critical skill that must be mastered in the 21st century to understand and participate effectively in a computer-driven world. Recently, the integration of STEAM-based learning and the use of educational media applications have emerged as strategic approaches to foster CT development. To evaluate the extent to which CT is successfully cultivated through STEAM learning processes, a valid and reliable test instrument is required. This study aims to develop a CT test instrument based on the ClassPoint application within a STEAM project framework. The research employs a development methodology using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were university students enrolled in a Discrete Mathematics course. The test instrument was reviewed by subject matter experts and media experts. Content validity was assessed using Aiken’s V index, while item validity, reliability, and difficulty level were analyzed using the Rasch model with the Winsteps software. The results indicate that the instrument possesses high content validity, strong reliability (Cronbach’s Alpha = 0.89), and a well-distributed range of item difficulty levels. Therefore, the developed instrument is deemed suitable for effectively and efficiently measuring students’ Computational Thinking abilities in the context of STEAM-based learning supported by interactive technology.